Conceptions of Healthy Aging Held by Relatives of Older Persons in Isan-Thai Culture: A Phenomenographic Study - Pornpun Manasatchakun; Åsa Roxberg; Margareta Asp (Journal of Aging Research)
In Thailand, family nurses are expected to provide support for older persons and their family members to promote healthy aging. Family bonds are strong, and relatives are expected to take care of their older family members. However, there is limited research on how older persons’ family members perceive healthy aging. This study aimed to describe the conceptions of healthy aging held by the children and grandchildren of older persons in northeast Thailand. In a phenomenographic study, 14 interviews were performed to qualitatively analyze different conceptions of healthy aging. Four descriptive categories emerged: being independent, not being afflicted by diseases or illnesses, being a giver and a receiver, and being wise. The conceptions of healthy aging entail both autonomy and interdependence. The relative’s perspective needs to be considered when policies relating to healthy aging are implemented in the community and when family nurses provide support to families to promote healthy aging.